The effect of management accounting information system and budget participation on managerial performance with financial technology as a moderating variable - Baihaqi Ammy (Trigin Publisher, 2025)
This study aims to test and analyze the influence of management accounting information systems and managerial performance on managerial performance with financial technology as a moderating variable at the DPRD office of South Tapanuli Regency. This study uses a quantitative approach with an associative design. Data collection was carried out by collecting primary data in the form of questionnaires by distributing questionnaires to employees in the accounting and finance departments at the DPRD office of South Tapanuli Regency. The sampling technique used in the study used saturated samples with a total of 36 samples obtained. The data analysis technique used to test the hypothesis in this study was Moderated Regression Analysis with the help of IBM SPSS software version 27. The results of this study indicate that management accounting information systems have a positive and significant effect on managerial performance, participation has a positive and significant effect on managerial performance, financial technology significantly moderates the effect of management accounting information systems on managerial performance, and financial technology does not moderate the effect of budget participation on managerial performance.